2011
DOI: 10.1007/s00441-010-1109-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular morphology and markers of cartilage and bone in the marine teleost Sparus auratus

Abstract: Modifications have been characterised in terms of cellular organisation and the extracellular matrix (ECM) during bone ontogeny in the sea bream (Sparus auratus). During endochondral development, the agglomeration of matrix-secreting cells gives rise to chondrones; these chondrones frequently contain proliferating-cell-nuclear-antigen-positive cells, which subsequently become large collagen-II-positive cells with the characteristics of chondrocytes. Moreover, the matrix:cell ratio within the perichondrium incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 71 publications
(102 reference statements)
1
23
0
Order By: Relevance
“…2 [81] reports that dentary ossifies endochondrally but being the only reference affirming this, this bone has been inserted among the intramembranously ossifying elements.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2 [81] reports that dentary ossifies endochondrally but being the only reference affirming this, this bone has been inserted among the intramembranously ossifying elements.…”
Section: Resultsmentioning
confidence: 98%
“…1hypurals are reported to ossify endochondrally in zebrafish ( Danio rerio ) [78][80], in Senegalese sole ( Solea senegalensis ) [80], in gilthead seabream [81] but other authors found that ossification is perichondral in Nile tilapia and desert pupfish [82];…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPARC has a key role in ECM assembly and deposition due to its binding to a number of different ECM components [53]. Controlled expression of this protein seems to be essential for normal osteoblastic differentiation and skeletogenesis in mammals [54][55][56] and fish [57][58][59]. In that sense, SPARC was shown to display several conserved features throughout evolution, mainly related to its protein structure, function and regulation [59].…”
Section: Mir-29a Promotes Ecm Mineralizationmentioning
confidence: 97%
“…Nevertheless, there is overall conservation of tissue organisation in vertebrates and the extracellular matrix (ECM) in teleosts contains homologues of mammalian ECM proteins, both collagenous and non-collagenous, such as osteonectin (OSN) and osteocalcin [8,17,29]. At the cellular level osteoblasts (bone forming cells) and osteoclasts (bone resorbing cells) are present in the bone of advanced teleosts but in contrast to osteocyte-containing mammalian bone, it is acellular, with a few notable exceptions eg.…”
Section: Introductionmentioning
confidence: 99%